Between Growth and Green: Rethinking the Politics of Decoupling in Emerging Economies - Muhammad Qeyas (Universitas Muhammadiyah Purwokerto, 2025)
With the rising environmental crisis, guided by growing economic interests, the notion of decoupling economic growth and environmental degradation has become a mainstream idea across the world. A sense of pressure is emerging in economies like Indonesia, which are compelled to grow by complying with sustainability goals, highlighting a profound need to re-evaluate whether decoupling is a viable and fair approach. This paper examines the political, structural, and institutional feasibility of absolute decoupling by conducting a comparison between policy frameworks in developed and emerging economies, such as Denmark, Sweden, China, and Indonesia. The study employs a qualitative comparative policy analysis and thematic review to discuss how green growth approaches, including the concepts of a circular economy and transitions to renewable energy, are converted into practice. The results indicate that while countries such as Denmark and Sweden has made notable progress, Indonesia continues to face structural barriers, policy incoherence, and budgetary constraints. The research indicates that the concept of decoupling, as it is presented, is possibly a type of ecological idealism that overlooks history, economics, and geopolitics in the Global South. It proposes a new understanding of prosperity, advocating an understanding of sustainability that has a justice orientation beyond GDP-oriented growth. Decoupling should move beyond a technical undertaking to a political initiative, one based on planetary boundaries, socio-economic fairness, and post-colonial political independence.